Just grazing the surface: A tribute to Professor John Hodgson 1937–2018. (9th December 2018) - Hodgson, David J.; Lemaire, Gilles; Matthew, Cory; Montossi, Fabio; Nan, Zhibiao; Ren, Jizhou; Da Silva, Sila
Abstract: John Hodgson (1937–2018) is renowned worldwide as a passionate and principled researcher, dedicated to the study of interactions between grazing livestock and pasture sward, and to whole‐system management of grassland. He published over 250 scientific outputs during his 50‐year career, and inspired generations of grazing ecologists. Following his upbringing on a mixed‐livestock farm in the Yorkshire Dales, John received BSc, PhD and DSc from the University of Leeds, UK. He worked in research institutes in Hurley, England and Penicuik, Scotland, before taking a Chair in Agronomy at Massey University, New Zealand in 1986. There, he progressed to become Head of School for the Environment. John retired from university life in 2002, but never left academia. John's global research legacy is reflected in the international authorship of this memorial review. His international impact is demonstrated by the supervision of over 50 PhD students from all over the world, and by his knowledge‐sharing travels to South America and China. His peers will remember him as a thoughtful and collaborative scholar. His students will remember him as an inspiring and caring mentor. He helped to revolutionize the way that grasslands are managed, in the face of global environmental change and increasing demand on grazed systems. John lost a long battle with Parkinson's disease in October 2018 and is survived by his wife, Ruth, and five children. His own research was often dedicated to his father, Dick Hodgson, and the first author of this tribute wishes to do the same.